Gestures in Language Instruction: Bridging The Gap for Effective Correction and Learning - Maruf, Nirwanto; Husain, Dahlia; Mujayanah, Sri; Aprilia Tiana, Ella; Hadi Santoso, Kusumo (LP2M IAIN Sultan Amai Gorontalo, 2024)
This study investigates the impact of integrating innovative gestures into language instruction at Universitas Muhammadiyah Gresik (UMG) and Universitas Muhammadiyah Gorontalo (UMGO). The primary objective was to assess how various types of gestures, including interactive digital boards, emotional expression, dynamic movement sequences, gamified approaches, and multimodal feedback gestures, influence student engagement, comprehension, and retention. Through observational data and semi-structured interviews with language lecturers, the study provides comprehensive insights into the efficacy of gesture-based teaching methods. The results reveal that the use of gestures significantly enhances the visibility and impact of corrective feedback, making linguistic errors more noticeable and facilitating better understanding and retention compared to traditional verbal feedback methods. Observational data indicate that students are more actively involved in discussions and activities when gestures are used, leading to a more dynamic and interactive classroom environment. This increased engagement highlights the potential of gestures to improve comprehension and cognitive processing in language learning. Semi-structured interviews with lecturers further emphasize the perceived benefits of gestures, such as enhanced engagement, improved comprehension, and better retention of language skills. However, challenges including technological limitations, the need for professional development, and time constraints were also identified. To address these challenges, educators recommended strategies like gradual implementation of gestures, soliciting student feedback, and combining gestures with other multimedia resources. In conclusion, this study demonstrates that integrating gestures into language instruction can significantly enhance learning outcomes by making lessons more engaging and effective. Future research should focus on long-term impacts and the development of training programs to support educators in adopting gesture-based teaching methods.